A combined compromise solution (CoCoSo) method for multi-criteria decision-making problems. Issue 9 (23rd November 2018) - Yazdani, Morteza; Zarate, Pascale; Kazimieras Zavadskas, Edmundas; Turskis, Zenonas
Abstract : Purpose: The purpose of this paper is to discuss the advantage of a combinatory methodology presented in this study. The paper suggests that the comparison with results of previously developed methods is in high agreement. Design/methodology/approach: This paper introduces a combined compromise decision-making algorithm with the aid of some aggregation strategies. The authors have considered a distance measure, which originates from grey relational coefficient and targets to enhance the flexibility of the results. Hence, the weight of the alternatives is placed in the decision-making process with three equations. In the final stage, an aggregated multiplication rule is employed to release the ranking of the alternatives and end the decision process. Findings: The authors described a real case of choosing logistics and transportation companies in France from a supply chain project. Some comparisons such as sensitivity analysis approach and comparing to other studies and methods provided to validate the performance of the proposed algorithm. Originality/value: The algorithm has a unique structure among MCDM methods which is presented for the first time in this paper.